1981
DOI: 10.2307/3808098
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Husbandry Methods and Sheep Losses to Canine Predators

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.Allen Press is collaborating with JSTOR to digitize, preserve and extend access to The Journal of Wildlife Management. Abstract: In this study we evaluated the efficacy of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 8 publications
1
24
0
1
Order By: Relevance
“…A negative association has been also reported between carnivore predation on livestock and the density of roads and human settlements (Robel et al 1981;Stahl et al 2001). Our analysis shows that in Finland, wolf attacks on sheep farms are most likely to occur in the mosaic of forest, small wetland, clear cuts and plantations.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…A negative association has been also reported between carnivore predation on livestock and the density of roads and human settlements (Robel et al 1981;Stahl et al 2001). Our analysis shows that in Finland, wolf attacks on sheep farms are most likely to occur in the mosaic of forest, small wetland, clear cuts and plantations.…”
Section: Discussionmentioning
confidence: 52%
“…Wolves seem to avoid areas with a large proportion of agricultural and built-up landscapes. In United States, placing pastures around vegetated waterways may promote coyote (Canis latrans) predation on sheep (Robel et al 1981). We found that in Finland, small areas of wetland and water were somewhat attractive to wolves, but when the size of these landscape classes grew they started to have a slight negative impact on the probability of depredation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As entrevistas vêm sendo freqüentemente utilizadas para avaliar as perdas causadas por predadores e fornecer informações sobre a percepção da população em relação ao conflito (por ex., ver Robel et al 1981, Schaefer et al 1981, Oli et al 1994, Manzatti 1999, Mazzolli et al 2002, Conforti & Azevedo 2003, Palmeira 2004, Zimmermann et al 2005, Michalski et al 2006 Para quantificar a predação por onças e levantar a opinião local em relação ao conflito foram realizadas entrevistas semi-estruturadas em 28 propriedades, representando 87% do total de propriedades existentes nas duas comunidades (Figura 2). As entrevistas foram realizadas apenas com o responsável de cada propriedade selecionada.…”
Section: Entrevistasunclassified
“…For example, husbandry practices such as gathering livestock into protected areas during vulnerable times (e.g., shed lambing or night penning) are tools that owners have used for hundreds of years to protect livestock (Robel et al 1981, Wagner 1988, Ogada et al 2003.…”
Section: Tools and Conceptsmentioning
confidence: 99%